2016
DOI: 10.1038/labinvest.2015.157
|View full text |Cite
|
Sign up to set email alerts
|

PIK3C2A is a gene-specific target of microRNA-518a-5p in imatinib mesylate-resistant gastrointestinal stromal tumor

Abstract: Imatinib mesylate resistance occurs in some patients with gastrointestinal stromal tumors (GISTs) during the course of treatment. In this study, we investigated the relationship between microRNAs (miRNAs) and imatinib-resistant GISTs, and the effect of miR-518a-5p on PIK3C2A in imatinib-resistant GISTs. A total of 20 matched-pair GIST samples from imatinibresistant patients were included in the study. Each of the paired tumor specimens were from the same patient who had surgical removal of GISTs preimatinib an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 29 publications
3
32
0
1
Order By: Relevance
“…Another study reports that apoptosis induced by miR-518a-5p affected the cellular response to the drug, causing imatinib resistance in GIST. 31 We have also found previously that STIM1-mediated SOCE contributes to apoptosis via phosphorylation of the MEK/ERK pathway, which is a classical signaling pathway that participates in cell growth, EMT and apotosis. 32 STIM1-knockdown cells in the present study had lower levels of phosphorylated MEK and ERK than that of control cells, whereas total protein levels were unaffected.…”
Section: Discussionsupporting
confidence: 61%
“…Another study reports that apoptosis induced by miR-518a-5p affected the cellular response to the drug, causing imatinib resistance in GIST. 31 We have also found previously that STIM1-mediated SOCE contributes to apoptosis via phosphorylation of the MEK/ERK pathway, which is a classical signaling pathway that participates in cell growth, EMT and apotosis. 32 STIM1-knockdown cells in the present study had lower levels of phosphorylated MEK and ERK than that of control cells, whereas total protein levels were unaffected.…”
Section: Discussionsupporting
confidence: 61%
“…Another report showed that miR-7 could work in synergy with imatinib to sensitize K562 (456). As the last ncRNA in this subnetwork, miR-518a is down-regulated in imatinib-resistant gastrointestinal stromal tumor (GIST) and PIK3C2A was identified as the relevant specific target (457). …”
Section: Drugs/non-coding Rnas Subnetworkmentioning
confidence: 99%
“…MIR17, MIR20A, MIR221-MIR222 ! mimics as a promising approach in TKI-resistant GIST [106]. MIR518A-5p !…”
Section: Abbreviationsmentioning
confidence: 99%
“…105 Recently, Shi and collaborators reported a correlation between MIR518A-5p and apoptosis. 106 The authors found MIR518A-5p downregulation in imatinib-resistant GIST patients by miRNA microarray and provided evidence of a functional interaction with the 3 0 UTR of the PIK3C2A gene. The PIK3C2A gene belongs to the phosphatidylinositol (PtdIns) 3-kinase family, which regulates various cellular processes, including cell growth, proliferation and apoptosis.…”
mentioning
confidence: 92%
See 1 more Smart Citation